2021
DOI: 10.1021/acs.jafc.1c05239
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Exerts Beneficial Effects on Hyperuricemia by Inhibiting Xanthine Oxidase and NLRP3 Inflammasome Activation

Abstract: Hyperuricemia is a metabolic disease caused by impaired uric acid (UA) metabolism. Ellagic acid (EA) is a natural small-molecule polyphenolic compound with known antioxidative and anti-inflammatory properties. Here, we evaluated the regulatory effects of EA on hyperuricemia and explored the underlying mechanisms. We found that EA is an effective xanthine oxidase (XOD) inhibitor (IC50 = 165.6 μmol/L) and superoxide anion scavenger (IC50 = 27.66 μmol/L). EA (5 and 10 μmol/L) treatment significantly and dose-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…Methanolic extract was able to inhibit xanthine oxidase enzyme with an IC50 of 557.77 μg/ml ( Chong and Loh, 2020 ). Phytomolecules like kaempferol ( Wang et al, 2015d ), quercetin ( Bindoli et al, 1985 ), stigmasterol ( Chiang and Chen, 2008 ), ellagic acid ( Sun et al, 2021 ), ferulic acid ( Nile et al, 2016 ), and chlorogenic acid ( Wang et al, 2009 ) may be responsible for the antigout potential of Alternanthera sessilis (L.) R.Br. ex DC.…”
Section: Introductionmentioning
confidence: 99%
“…Methanolic extract was able to inhibit xanthine oxidase enzyme with an IC50 of 557.77 μg/ml ( Chong and Loh, 2020 ). Phytomolecules like kaempferol ( Wang et al, 2015d ), quercetin ( Bindoli et al, 1985 ), stigmasterol ( Chiang and Chen, 2008 ), ellagic acid ( Sun et al, 2021 ), ferulic acid ( Nile et al, 2016 ), and chlorogenic acid ( Wang et al, 2009 ) may be responsible for the antigout potential of Alternanthera sessilis (L.) R.Br. ex DC.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported an effect of EA upregulating endothelial nitric oxide synthase and restoring nitric oxide bioavailability [ 17 ]. Another study reported a direct effect of EA, reducing uric acid synthesis by inhibition of xanthine oxidase [ 46 ]. This inhibition reduces tissue injury, target-organ damage, and cardiovascular risks [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported a direct effect of EA, reducing uric acid synthesis by inhibition of xanthine oxidase [ 46 ]. This inhibition reduces tissue injury, target-organ damage, and cardiovascular risks [ 46 ]. An important related fact is that in a long-term cohort for mortality analysis, it was identified that uric acid > 5.1 mg/dL (303 µmol/L) in females, or >5.6 mg/dL (333 µmol/L) in males, can be a predictor of cardiovascular mortality with linear association between serum uric acid and increased risk of all-cause mortality and cardiovascular mortality [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…PG tissues were fixed in 10% formalin, embedded in paraffin, and sliced into sections of thickness 5 μm. Then, they were stained with hematoxylin and eosin (H&E) for general morphological evaluation under a light microscope (Olympus, Tokyo, Japan), as reported previously [ 30 ].…”
Section: Methodsmentioning
confidence: 99%